2009
DOI: 10.1007/s00198-009-1079-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of oral bisphosphonate prescriptions in post-menopausal women with osteoporosis in a real-world setting in the USA

Abstract: SummaryWe identified factors associated with oral bisphosphonate treatment in 50+-year-old female patients with a first fracture, osteoporosis diagnosis, or BMD ≤−2.5 in the Geisinger Health System electronic health record database. Treatment was positively associated with age, oral corticosteroids, and smoking, and negatively associated with body mass index and bone mineral density scores.IntroductionTo identify factors associated with oral bisphosphonate treatment in patients with an indicator for post-menop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…Hamel et al reported that a finding of osteoporosis or osteopenia by first BMD testing influenced the prescribing of bisphosphonates, while a pretest history of fracture did not[15]. Asche et al also examined predictors of oral bisphosphonate prescriptions in postmenopausal women, and found that fracture history, older age, low T-score (≤–2.5), and oral corticosteroid use were associated with treatment with an oral bisphosphonate [16]. Onder et al studied patients with a diagnosis of osteoporosis who were discharged from hospital [17].…”
Section: Discussionmentioning
confidence: 99%
“…Hamel et al reported that a finding of osteoporosis or osteopenia by first BMD testing influenced the prescribing of bisphosphonates, while a pretest history of fracture did not[15]. Asche et al also examined predictors of oral bisphosphonate prescriptions in postmenopausal women, and found that fracture history, older age, low T-score (≤–2.5), and oral corticosteroid use were associated with treatment with an oral bisphosphonate [16]. Onder et al studied patients with a diagnosis of osteoporosis who were discharged from hospital [17].…”
Section: Discussionmentioning
confidence: 99%
“…Results from multiple studies suggest that the methods used to identify OP and treatment for OP may influence the level of treatment penetration observed. In a study of self-reported OP patients, 54.9% reported receiving treatment 33 , while a study that compared treatment rates by the method of OP identification observed that 9.4% of patients identified through the occurrence of a fracture received treatment within 90 days, while among patients identified via ICD-9-CM diagnosis or the presence of a bone-mineral density test, the percentage treated within 90 days was 41.6% 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, older patients were less likely to receive OP treatment 16,20 , although BP treatment appears to be more likely as age increases 20,28 . Other factors that have been reported to have a positive association with receiving OP treatment include lower body mass index 28,33 and lower disease burden 33 , including lower incidence of chronic inflammatory joint disease, hypertension, and diabetes 20 . These studies parallel our results which suggest that patients with higher disease burden, comorbid hypertension and diabetes, and patients who were obese were less likely to receive OP treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Denmark an increasing trend of alendronate treatment in patients with systemic GC exposure was found, indicating increased awareness of GIOP [106]. However, in another study on postmenopausal women with osteoporosis, many patients were untreated [107]; similarly, bone health-related care was found suboptimal in specific patients groups [108], such as a community-based cohort of SLE patients [109], and RA patients using GCs [110]. On average, approximately 27-40% of those who should receive a prescription for bone protective drugs receive one [111,112].…”
Section: Stage 0: Awareness Agreement and Infrastructurementioning
confidence: 99%